Politik Islam dalam Konteks Tunisia Pasca Revolusi Jasmine: Analisis Pemikiran Rashid Ghannoushi: Political Islam in The Post-Jasmine Revolution Context of Tunisia: Analyzing the Thoughts of Rashid Ghannoushi - A. Rahman, M.Zaidi; Tumin, Makmor; Zainal Abidin, Azmil (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
Tunisia has a unique experience as the first Arab country to spark the Arab Spring. This uprising was filled with a series of anti-government protests called the Jasmine Revolution. In that situation, Rashid Ghannoushi, the head of the Islamic Movement in Tunisia (Al-Nahdah) was also involved in the situation by putting his perspective based on the party’s Islamic agenda. So, the objective of this article is to trace the political thought of Rashid Ghannoushi in achieving political goals through the framework of Islamic politics. This is because the results of his thought on political Islam show a significant difference with other Islamic movements especially in the context of managing power sharing. The results of the study found that his political views take into account local factors such as autocratic leadership and the secular doctrine of laicite, that inspired him to consider between the ideal of Islamic doctrine and the realistic of the atmosphere and situation in Tunisia.